1997
DOI: 10.1103/physrevlett.78.4273
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy Observation of a Square Abrikosov Lattice inLuNi2B2C

Abstract: We present scanning tunneling microscopy measurements of the (001) surface of a LuNi 2 B 2 C borocarbide single crystal at 4.2 K. In zero field, the conductance versus voltage characteristics recorded at various locations on the sample reproducibly provide a gap value of 2.2 meV. In a magnetic field of 1.5 and 0.375 T, the recordings of the conductance as a function of position reveal a regular square vortex lattice tilted by 45 ± with respect to the crystalline a axis. This unusual result is correlated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 27 publications
11
111
0
Order By: Relevance
“…The gradual transition from the triangular to the square vortex lattice is also observed with increasing field. 23,43 As µSR and SANS experiments have begun on these materials, we expect that the d x 2 −y 2 -wave-like nature will be detected there.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual transition from the triangular to the square vortex lattice is also observed with increasing field. 23,43 As µSR and SANS experiments have begun on these materials, we expect that the d x 2 −y 2 -wave-like nature will be detected there.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As for the orientation of the triangular lattice, the case θ 0 = 45 • has a smaller F than the case θ 0 = 0 • , but the difference is very small. Some theoretical calculations considered the vortex lattice configuration near H c2 , [21][22][23] or based on the London theory. [24][25][26] These theories suggested that the vortex lattice configuration gradually changes from the triangular lattice to the square lattice with increasing field, and the oblique lattice is realized at a lower field before settling into the square lattice.…”
Section: Vortex Lattice Configurationmentioning
confidence: 99%
“…One of the interesting features of some borocarbides (R=Er, Lu, Y) is the vortex lattice (VL) with unusual square symmetry [11][12][13][14] observed in the mixed state for magnetic fields H directed along tetragonal c-axis at H > ∼ 1 kOe. Square symmetry of VL can be connected 11,8 with the anisotropy of the upper critical magnetic field H c2 (T ) observed in the ab-plane for LuNi 2 B 2 C. 8,9 Practically no anisotropy of H c2 (T ) was found for YNi 2 B 2 C, 6,9 although this compound is very similar to LuNi 2 B 2 C. The reason for the difference in the behavior of these two borocarbides is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Gurevich-Kogan non-local London model, 14 the anisotropic nonlocal potential, which is responsible for the low-field FLL transition observed in SANS, 9 is averaged out by thermal vortex fluctuations near H c2 . Since the interaction becomes isotropic, the hexagonal Abrikosov lattice is preferable, leading to the second FLL transition from square back 28,29 The diamonds are SANS data, where the numbers next to the data indicate the degrees of the azimuthal splitting with which the transition line is determined. 9 The square and rhombic shapes are forms of vortex lattices.…”
mentioning
confidence: 99%